Phylogenetic relationships and lineage-specific mitochondrial gene rearrangement in Ophiuroidea: insights from mitochondrial genomes - Na, Jieying; Zhou, Yadong; Cheng, Hong; Zhang, Ruiyan; Shen, Chengcheng; Lu, Bo; Wang, Chunsheng; Zhang, Dongsheng (Frontiers in Marine Science, 2024)
Ophiuroids, the most diverse group of echinoderms, inhabit a vast array of ecological niches and play vital roles in benthic ecosystems as suspension feeders, scavengers and opportunists. Despite the important ecological roles played by Ophiuroidea, their evolutionary history and phylogenetic relationship is not yet fully understood. In this study, 47 mitochondrial genomes of ophiuroids, including 21 newly sequenced ones, were analyzed. tRNA duplication was firstly discovered in four species and a new start codon was identified for Ophiuroidea. Eighteen phylogenetic trees based on mitochondrial genomes consistently supported two major lineages, Ophintegrida and Euryophiurida. It further confirmed the monophyly of Euryalida and Ophiurida, respectively, as well as families represented by multiple species. Among 18 trees, only the two ML trees based on amino acid sequences using IQtree method supported monophyly of Amphilepidida and Ophiacanthida, consistent with current phylogenetic system of Ophiuroidea. This result highlighted the effect of phylogenetic analysis methods and datasets on tree topology, indicating that amino acid sequence data maybe more suitable for higher taxonomic level phylogenetic analysis of ophiuroids than nucleotide sequences. Four new gene orders of 13 protein-coding genes + two rRNAs and 12 new gene orders of all 37 genes were identified. Mitochondrial gene orders were highly variable in Ophiacanthida, but were extremely conserved in Eurylida. Additionally, both branch lengths and estimated positive selection varied among the four orders, and a positive relationship between branch lengths and mitochondrial gene rearrangement rates was revealed, suggesting distinctly different evolutionary history among the four major clades of Ophiuroidea. Overall, we (1) reconstructed the phylogenetic relationship based on mitochondrial genome, supporting the current phylogenetic system in Ophiuroidea, (2) revealed a high variability in mitochondrial gene rearrangement among the four orders, (3) provided the first evidence to link gene rearrangement and nucleotide substitution in Echinodermata.